Selling the Scandinavian Ethos: Principal Marketing Strategies of Nordic Design Brands - Wiśnicka, Anna (Stan Rzeczy, 2023)
This text presents and analyses the principal marketing strategies used by Danish, Swedish, and Finnish companies and describes the set of marketing messages characteristic of Scandinavian design brands. The most popular strategies involve geo-recognition, with sociolinguistic mechanisms that influence the names of companies and products and the self-description of brands. The contradictory issues of nobilitation and egalitarianism, which have a pivotal role in the advertising of specific products for different groups of recipients, are addressed. Co-branding, including image collaborations between brands operating in different sectors, and mass media influence (the leading tool of advertisement, through films, series, and TV commercials), are other strategies. Connections are established between design promotion and widely recognisable cultural phenomena, such as hygge or lagom. Analysis reveals that the main marketing strategies characteristic of the design brands of the North revolve around a multitude of connections to Scandinavian heritage and culture.